Geographical variation in the incidence of childhood leukaemia in Manitoba. (3rd June 2015) - Torabi, Mahmoud; Singh, Harminder; Galloway, Katie; Israels, Sara J
Abstract : Background: Identification of geographical areas and ecological factors associated with higher incidence of childhood leukaemias can direct further study for preventable factors and location of health services to manage such individuals. Aim: The aim of this study was to describe the geographical variation and the socio‐demographic factors associated with childhood leukaemia in Manitoba. Methods: Information on childhood leukaemia incidence between 1992 and 2008 was obtained from the Canadian Cancer Registry and the socio‐demographic characteristics for the area of residence from the 2006 Canadian Census. Bayesian spatial Poisson mixed models were used to describe the geographical variation of childhood leukaemia and to determine the association between childhood leukaemia and socio‐demographic factors. Results: The south‐eastern part of the province had a higher incidence of childhood leukaemia than other parts of the province. In the age and sex‐adjusted Poisson regression models, areas with higher proportions of visible minorities and immigrant residents had higher childhood leukaemia incidence rate ratios. In the saturated Poisson regression model, the childhood leukaemia rates were higher in areas with higher proportions of immigrant residents. Unemployment rates were not a significant factor in leukaemia incidence. Conclusion: In Manitoba, areas with higher proportions of immigrants experience higher incidence rates of childhood leukaemia. We have identified geographical areas with higher incidence, which require further study and attention.